Algal Export in the Arctic Ocean in Times of Global Warming - Lalande, Catherine; Nöthig, Eva‐Maria; Fortier, Louis (Geophysical research letters, 2019)
Satellite‐derived data suggest an increase in annual primary production following the loss of summer sea ice in the Arctic Ocean. The scarcity of field data to corroborate this enhanced algal production incited a collaborative project combining six annual cycles of sequential sediment trap measurements obtained over a 17‐year period in the Eurasian Arctic Ocean. Here we present microalgal fluxes measured at ~200 m to reflect the bulk of algal carbon production. Ice algae contributed to a large proportion of the microalgal carbon export before complete ice melt and possible detection of their production by satellites. In the northern Laptev Sea, annual microalgal carbon fluxes were lower during the 2007 minimum ice extent than in 2006. In 2012, early snowmelt led to early microalgal carbon flux in the Nansen Basin. Hence, a change in the timing of snowmelt and ice algae release may affect productivity and export over the Arctic basins. Plain Language Summary An increase in algal production has been reported following the recent decline in sea ice cover in the Arctic Ocean. However, very few field measurements have been conducted to corroborate these remote sensing‐derived observations. Algal cell fluxes collected with sediment traps at ~200 m during six annual cycles between 1995 and 2012 were combined to determine changes in the timing, magnitude, and composition of the algal export in the Eurasian Arctic Ocean. Algal fluxes, mostly composed of ice algae, reflected a large fraction of the surface phytoplankton carbon production. Ice algae were nearly all collected during snowmelt and before complete ice melt, preventing the detection of their production by satellites. While relatively high algal export was observed under thick ice cover in 1996, early algal export in 2012 suggested an early release of ice algae due to early snowmelt. Overall, snow cover played an important role in regulating the timing and magnitude of ice algae release in the Eurasian Arctic Ocean. Key Points The majority of algal cells were exported before complete ice melt Early snowmelt led to the early release of ice algae prior to the record minimum sea ice extent of 2012 Phytoplankton carbon contributed up to ~40% of the particulate organic carbon fluxes during short intense export events